Early Outcomes of Three Total Arch Replacement Strategies for DeBakey Type I Aortic Dissection - Xie, Enzehua; Wu, Jinlin; Qiu, Juntao; Dai, Lu; Qiu, Jiawei; Luo, Qipeng; Jiang, Wenxiang; Cao, Fangfang; Zhao, Rui; Fan, Shuya; Gao, Wei; Guo, Hongwei; et al. (Frontiers in Cardiovascular Medicine, 2021)
BACKGROUND This study employed three surgical techniques: total arch replacement (TAR) with frozen elephant trunk (FET), aortic balloon occlusion technique (ABO) and hybrid aortic arch repair (HAR) on patients with type I aortic dissection in Fuwai Hospital, aiming to compare the early outcomes of these surgical armamentariums. METHODS From January 2016 to December 2018, an overall 633 patients (431 of TAR+FET, 122 of HAR, and 80 of ABO) with type I aortic dissection were included in the study. 30-day mortality, stroke, paraplegia, re-exploration and renal replacement therapy were compared using the inverse probability weighting method (IPW). RESULTS After IPW process, the baseline characteristics were comparable among three TAR groups. It showed that ABO group had the longest cardiopulmonary bypass (p < 0.001) and aortic cross-clamp time (p < 0.001), while the operation time was longest in the HAR group (p = 0.039). There was no significant difference in 30-day mortality among groups (p = 0.783). Furthermore, the incidence of stroke (p = 0.679), paraplegia (p = 0.104), re-exploration for bleeding (p = 0.313) and CRRT (p = 0.834) demonstrated no significant difference. Of note, no significant differences were found regarding these outcomes even before using IPW. CONCLUSIONS Based on the early outcomes, the three TAR approaches were equally applicable to type I aortic dissection. We may choose the specific procedure relatively flexibly according to patient status and surgeon’s expertise. Importantly, long-term investigations are warranted to determine whether above approaches remain to be of equivalent efficacy and safety.